2018
DOI: 10.1038/s41467-018-05176-7
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated NDR1 protein kinase inhibits innate immune response by initiating an miR146a-STAT1 feedback loop

Abstract: Interferon (IFN)-stimulated genes (ISGs) play crucial roles in the antiviral immune response; however, IFNs also induce negative regulators that attenuate the antiviral response. Here, we show that both viral and bacterial invasion downregulate Nuclear Dbf2-related kinase 1 (NDR1) expression via the type I IFN signaling pathway. NDR1 promotes the virus-induced production of type I IFN, proinflammatory cytokines and ISGs in a kinase-independent manner. NDR1 deficiency also renders mice more susceptible to viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
(53 reference statements)
0
21
1
Order By: Relevance
“…Thioglycolate-elicited mouse primary peritoneal macrophages were prepared from female C57BL/6J mice (6-8 weeks of age) as described previously (Jiang et al, 2017). Adherent cells were used as mouse primary peritoneal macrophages after 2 h. Immortalized bone marrow-derived macrophages (iBMDMs) were maintained in RPMI-1640 medium supplemented with 10% FBS and 20 ng/ml macrophage colony-stimulating factor (PeproTech, Rocky Hill, NJ, USA) (Liu Z. et al, 2018). All cells were cultured at 37°C in a humidified incubator containing 5% CO2.…”
Section: Cell Culturementioning
confidence: 99%
“…Thioglycolate-elicited mouse primary peritoneal macrophages were prepared from female C57BL/6J mice (6-8 weeks of age) as described previously (Jiang et al, 2017). Adherent cells were used as mouse primary peritoneal macrophages after 2 h. Immortalized bone marrow-derived macrophages (iBMDMs) were maintained in RPMI-1640 medium supplemented with 10% FBS and 20 ng/ml macrophage colony-stimulating factor (PeproTech, Rocky Hill, NJ, USA) (Liu Z. et al, 2018). All cells were cultured at 37°C in a humidified incubator containing 5% CO2.…”
Section: Cell Culturementioning
confidence: 99%
“…Mechanistically, NDR1 increases the translation of the transcription factor STAT1 by directly linking to the intergenic region of miR146a. These new molecular findings show that IFN-dependent antiviral immune response, residing on NDR1 is an important molecular mechanism of viral infections control (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 81%
“…STAT1 translation subsequently increases the production of type I IFN, pro-inflammatory cytokines and interferon-stimulated genes (ISGs) for the antiviral immune response. These findings revealed that NDR1 positively regulates type I and type II IFN pathways and enhances antiviral immune response (6). Glycogen synthase kinase 3β (GSK3β) and STAT1 are important participants in the antiviral immune response.…”
Section: Ndr Regulates Pattern Recognition Receptor-mediated Innate Imentioning
confidence: 95%
“…NDR1 (Stk38) mainly distributes in the nuclei. NDR2, on the other hand, is defined as a cytoplasmic kinase (4)(5)(6)(7). In addition to a central kinase catalytic domain, NDR1 and NDR2 each has a conserved N-terminal regulatory domain (NTR) and a C-terminal hydrophobic motif (8).…”
Section: Introductionmentioning
confidence: 99%